Incidência, caracterização molecular, hematológica e clínica do subtipo S/Beta-Talassemia em coorte de crianças triadas pelo programa de Triagem Neonatal de Minas Gerais e acompanhadas na Fundação Hemominas - Érica Louback de Oliveira (2019)
The Sβ-thalassemia (Sβ-tal) is a hemoglobinopathy heterozygous, characterized by the presence of a βS allele associated with the beta-thalassemia allele.The residual HbA production level is the main predictor. Genetic modulators may influence na heterogeneity, such as haplotypes and co-inheritance of alpha thalassemia. The aim of the study was to estimate the incidence and describe molecular, hematological and clinical characteristics in a cohort of newborns with Sβ-tal in Minas Gerais and screened as part of the Neonatal Screening Program in the Brazilian state of Minas Gerais and treated at Hemominas Foundation. Mutations were identified by sequencing. Genotyping of βS and β-thal haplotype polymorphisms were performed by polymerase chain reaction (PCR) , and restriction fragment length polymorphism (RFLP) or sequencing. The identification of deletions and triplication of alpha globin genes were performed by multiplex gap-PCR. Identification of the Corfu deletion in patients with IVS-I-5 G>A was performed using multiplex ligation-dependent probe amplification (MLPA). The relative concentration of hemoglobin fractions was determined by high-performance liquid chromatography (HPLC) in the vast majority of cases. The incidence of 5-year Sβ-tal (2011-2015) was 1: 22.250 (53 cases in 1,179,389 NB; 95% CI 1: 17,530-1: 30,450); 29 newborns with Sβ 0 -tal (54.7%) and 24 with Sβ + -tal (45.3%). To describe the characteristics of Sβ-tal 89 children (83 families) with a mean age of 10.9 years. Were 14 mutations were identified. 89 children were included in the study with a mean age of 10,9 years and 14 mutations were identified; 22 (24,7%) with CD39 C> T; 16 (18,0%) IVS-I-1 G> A; 10 (11, 2%) IVS-I-6 T> C; 9 (10, 1%) -29 A> G; 8 (9,0%) IVS-I-110 G> A; 6 (6, 7%) IVS-I-5 G> A; 4 (4,5%) IVS-II-1 G> A; 3 (3,4%) IVS-II-844 C> A e IVS-II-839 T> C; 2 (2,2%) -88 C> T ; 2 (2,2%) -92 C> T; 2 (2,2%) IVS-II-849 A> G; and one (1,2%) each for -101 C> T; IVS-I-2 T> C, and poly A signal (AATAAA> AACAAA). In two cases of Sβ+ -Thal, no mutation was found. In the children with the mutation IVS-I- 5 G> A, the Corfu deletion was not detected. The incidence of Sβ-Thal in the state of Minas Gerais was 1:22,250 (53 cases in 1,179,389 newborns for 5 years, 2011-2015). The incidence for the Sβ0-Thal subtype was 1:40,670 and that for Sβ+Thal, 1:49,140. The most commos βS haplotypes were CAR and Benin, in this order. In relation to β- thalassemic haplotypes, the most prevalent were I, II and IV. As far as the co- inheritance of alpha thalassemia, 68 (79%) had wild genotype (αα/αα), 16 (18.6%) were α/-α3.7; one was -α3.7/-α3.7, and one had triplication of the alpha gene (αα/ααα-3.7). In general, the incidence of clinical events per 100 patient-years was similar for the Sβ0- Thal genotypes and for the IVS-I-110 G> A and IVS-I-5 G> A mutations. In the latter, the concentration of HbA by HPLC was null in all six children, being clinically severe. Clinical and laboratory status of the other Sβ+- Thal genotypes (Hb A above 10%) is so different that it is misleading to aggregate, as in some reports in the literature, all these mutations in a single group. We conclude that the relative incidence of Sβ-Thal in Minas Gerais represents approximately 6% of the total cases with sickle cell disease. The correct identification of the mutation helps in the prognosis of the disease and in the adoption of preventive measures, aiming at a better quality of survival for this group of patients.